2021
DOI: 10.33166/acdmhr.2021.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Employee Engagement in a Financial Institution

Abstract: The purpose of this paper is to determine the relationship between transformational leadership, employee voice, training and development, and employee engagement among employees in a financial institution in Kuala Lumpur, Malaysia by using social exchange theory in this study. Quantitative data were collected using survey design, for which 248 employees responded. These employees were sourced from the financial institution. Based on multiple linear regression analyses, this study finds that transformational le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…The result from the second hypothesis of this study, H2, is that training and development has no positive effect on employee engagement. This contradicts a previous study which showed that training and development positively affects employee engagement (Ibrahim et al, 2021). Our result also contradicts Afroz (2018), whose findings revealed that respondents had regularly engaged in training programs provided by their employer.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The result from the second hypothesis of this study, H2, is that training and development has no positive effect on employee engagement. This contradicts a previous study which showed that training and development positively affects employee engagement (Ibrahim et al, 2021). Our result also contradicts Afroz (2018), whose findings revealed that respondents had regularly engaged in training programs provided by their employer.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research has demonstrated that SET can influence organizational behavior, particularly when employees have spent the majority of their lives at work. Rewards for their efforts such as training, development, compensation, and recognition, should be provided (Ibrahim et al, 2021 ). This theory was established in studies that examined the impacts of perceived justice, human resource development and identification, and ethical climate on employee engagement and satisfaction (O'Connor and Crowley-Henry, 2019 ).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training plays uncountable roles in the banking sector of Bangladesh, from skill development to employee performance; moreover, it is recommendable that training should be included as a core part of the organizational policy (Ibrahim, Rodzi, & Zin, 2021). Gary Dessler defined training as the process of teaching new employees the basic skills they need to perform their jobs.…”
Section: Trainingmentioning
confidence: 99%
“…Development also reflects several concepts consisting of greater maturity, emotional development, and periodic corporate self-confidence improvement that can identify new competencies and skills needed by employees in running the company's business processes (Dachner, Ellingson, Noe, & Saxton, 2021). Training and development have significant implications for employee engagement (Abogsesa & Kaushik, 2018;Ibrahim, Rodzi, & Zin, 2021;Nasidi, Waziri, Sunday, & Halim, 2020;Siddiqui & Sahar, 2019). It is one of the main elements in successfully implementing employee engagement.…”
Section: Introductionmentioning
confidence: 99%